Trypanosoma cruzi defined antigens in the serological evaluation of an outbreak of acute Chagas disease in Brazil (Catolé do Rocha, Paraíba) - Eufrosina S Umezawa; Maria Aparecida Shikanai-Yasuda; Arthur Gruber; Vera L Pereira-Chioccola; Bianca Zingales (Memorias do Instituto Oswaldo Cruz, 1996)
Immunoglobulin G and M humoral response to recombinant protein B13 and glycoconjugate LPPG Trypanosoma cruzi defined antigens was evaluated by ELISA in 18 patients in the acute phase of Chagas disease, who were contaminated on the same occasion. LPPG showed 100% positivity detecting both IgM and IgG antibodies, while positivity of 55-65% was observed for B13. An epimastigote alkaline extract (EPI) also showed high sensitivity for acute IgM (100%) and IgG (90%) antibodies. However LPPG had better discriminatory reactivity since with EPI two patients showed negative IgG and several other sera presented OD values for IgG and IgM antibodies very close to the cutoff. Thus, it is suggested that detection of IgM antibodies by LPPG may be used for diagnosis of the acute phase of Chagas disease. An intense decline of IgG and IgM antibodies to the three antigens was observed in response to anti-T. cruzi chemotherapy in all acute phase patients. After treatment, six (30%) individuals maintained IgG positivity to EPI, LPPG, and B13 with lower reactivity than that measured at the acute phase. For comparison, serology of a group of 22 patients in the chronic phase of Chagas disease and also submitted to chemotherapy was determined. Positive IgM antibodies to EPI, LPPG and B13 were detected in only 5-9% cases. In all chronic-phase patients IgG antibodies highly reactive to the three antigens were present and no significant decrease resulted after benznidazole administration. These observations reinforce previous reports that treatment in the acute phase may reduce or eliminate the parasite.